Analysis of economic structure in water buffalo breeding by geographical regions in Turkey - Karlı, Bahri; Gül, Mevlüt; Akpınar, Metin Göksel; Taşcıoğlu, Yavuz; Bozkurt, Yalçın; Şirikçi, Bekir Sıtkı (Buffalo Bulletin, 2021)
In this study, the status of water buffalo breeding in each geographical region in Turkey was examined, and the activities of enterprises were analysed from technical and economic perspectives. Four regions and the cities in these regions where buffalo breeding was concentrated in Turkey were chosen by Purposive Sampling Method, considering the number of water buffaloes, milk production and their share in the buffalo population and buffalo milk production in Turkey. A total of 462 sample enterprises were chosen from these cities by Stratified Random Sampling Method. The research data were collected through the questionnaires administered in face-to-face interviews with the producers. The data collected reflect the buffalo production in Turkey in 2014. The study examined socio-economic structures of the enterprises, revealing their capital structures and annual economic activities. The Marmara region ranked first in the time spent in buffalo breeding (26.62 years). Gross profit income was positive in four regions. Absolute profit and relative profit indicators were negative for farms in the Black Sea region and favourable for farms in other regions. For the development and promotion of buffalo breeding, the breeders should be further educated about better breeding practices; small enterprises should be modernized and expand their operations; efforts for the betterment of breeding practices should be intensified; existing wetlands should be protected and enhanced; the production costs (feed cost etc.) should be reduced; state subsidies should be granted to real producers; the public should be educated about the high nutritional value of water buffalo meat and milk through promotional campaigns, and buffalo producers should be better organized in producer unions.